Speech quality in lossy multiplexing - Shah, Asadullah; Bhatti, Zeeshan (IIUM Press, 2011)
Speech quality in multiplexing suffers due to various factors, including forced packet dropping. If a packet or segment ofspeech is dropped from any source by selecting users on random bases, and incidentally the randomly selected packet is perceptually sensitive, a single packet drop can cause a significant degradation is the quality both objectively and subjectively. To combat such problem a criterion based packet dropping produce better results. In this chapter speech quality in multiplexing situations both objectively and subjectively is explai